ADCP current measurements (75 kHz) during RV METEOR cruise M169 - Robert Kopte; Andrea Koschinsky; Katja Schmidt (PANGAEA, 2021)
Upper-ocean velocities along the cruise track of Meteor cruise M169 were continuously collected by a vessel-mounted Teledyne RD Instruments 75 kHz Ocean Surveyor ADCP. The transducer was located at 5.0 m below the water line. The instrument was operated in broadband mode with 4 m bins and a blanking distance of 4.0 m, while 50 bins were recorded using a pulse of 0.80 s. The ship extquotesingles velocity was calculated from position fixes obtained by the Global Positioning System (GPS). Heading, pitch and roll data from the ship extquotesingles gyro platforms and the navigation data were used by the data acquisition software VmDas internally to convert ADCP velocities into earth coordinates. The ADCP was set to record bottom-track velocities in addition to water velocities. For each single ping, the bottom-track velocity components were substracted from the velocity profile to obtain ocean currents. The average interval was set to 60 s.